Disability Focal Point Persons and Policy Implementation Across Sectors: A Qualitative Examination of Stakeholder Perspectives in Zambia - Cleaver, Shaun; Hunt, Matthew; Bond, Virginia; Lencucha, Raphael (Frontiers in Public Health, 2020)
Background: Zambia has created new disability policies and updated existing policies to be consistent with the United Nations Convention on the Rights of Persons with Disabilities. These initiatives require the widespread engagement of ministries and departments to achieve effective policy development and implementation. To pursue widespread engagement, the Government of Zambia developed a structure of disability focal point persons (FPPs). The Zambian disability FPP structure has not yet been explored systematically. Objective: To explore disability policy stakeholder perspectives about FPPs as a feature of disability policy development and implementation. Methods: We conducted semi-structured interviews with 24 disability policy stakeholders (10 policymakers, 2 researchers, and 12 disability advocates) as part of a larger study about the development and implementation of disability-related policies in Zambia. Interviews were audio recorded and transcribed. Data were analyzed using content analysis. Results: Participants presented FPPs as a promising way to mainstream disability within the government. According to participants, the initial launch of the FPP structure was ineffective, with a lack of clarity about the structure and an initial cohort of FPPs that wielded minimal influence. The FPP structure has since been revised. Participants express promise that the improved second launch will achieve mainstreaming. Discussion: Zambian disability policy stakeholders describe a disability FPP structure that is different from the models suggested for treaty implementation. Pre-established commitments to mainstreaming among stakeholders might have stimulated interest in following the cyclical development of the disability FPP structure, encouraging a whole-of-government approach to disability policy implementation.